2009
DOI: 10.1007/s00403-009-0933-y
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter protein is expressed in psoriasis, where it may play a role in regulating apoptosis

Abstract: Since the symptoms of psoriasis may be changed by treatment with selective serotonin reuptake inhibitors (SSRIs), the expression of serotonin (5-HT) and its transporter protein (SERT) in the skin of patients with psoriasis were examined employing a biotinylated-streptavidine procedure. In biopsies of such skin staining for 5-HT was limited to platelets; the expression of SERT in the keratinocytes of involved regions was redistributed; the numbers of SERT-positive dendritic or round mononuclear cells in the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…We also found that this protein colocalized with caspase-3, an apoptosis-regulating protein [9]. These findings suggest that the serotonergic system may be regulating the process of inflammation observed in psoriasis.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…We also found that this protein colocalized with caspase-3, an apoptosis-regulating protein [9]. These findings suggest that the serotonergic system may be regulating the process of inflammation observed in psoriasis.…”
Section: Introductionsupporting
confidence: 48%
“…The source population was all Swedish residents ever diagnosed with plaque psoriasis by dermatologists (ICD codes L40.0, L40.5 and L40. [8][9] and registered in the National Patient Register (inhospital care during 1997-2006 and outpatient care during [2001][2002][2003][2004][2005][2006] [12]. In total, 69 830 patients with plaque psoriasis were identified.…”
Section: Data Sources and Study Participantsmentioning
confidence: 99%
“…Serotonin was also detected by immunocytochemistry in dermal Merkel cells in rat and pig skin at the epidermal rete ridges and upper hair follicles adjacent to nerve terminals (Nordlind et al, 2008). Cutaneous serotonin content can be affected by inflammatory processes (Lonne-Rahm et al, 2008, Nordlind et al, 2008, Rasul et al, 2011, Thorslund et al, 2009). For example, human skin affected by psoriasis or chronic eczema showed elevated expression of serotonin in the epidermal and adnexal structures (Nordlind et al, 2007; 2008)…”
Section: Biogenic Amines In the Skinmentioning
confidence: 99%
“…14-16 An example of 5-HT mediated cutaneous neurogenic inflammation is its implication in atopic dermatitis 17,18 and psoriasis, [19][20][21] in addition to its significant role in initiating contact dermatitis. 22 5-HT is also implicated in several physiological functions as well as pathological conditions.…”
Section: Introductionmentioning
confidence: 99%